Deep-Sea Vector Geomagnetic Observations from a Mooring Platform: Instrument Demonstration and Geophysical Data Quality - Xianfeng Li; Chenguang Liu; Qingjie Zhou; Yang Sun (Journal of Marine Science and Engineering, 2026)
Despite their importance for constraining lithospheric magnetization models, tracking secular variation in oceanic regions, and improving global geomagnetic field representations, long-term vector geomagnetic data from deep-sea environments remain scarce. In this study, we developed a three-axis fluxgate magnetometer mounted on a deep-sea mooring platform to acquire continuous vector data at 580 m depth in the Western Pacific Ocean and assessed its performance through a 48 h observatory comparison and a 20-day at-sea trial. During the observatory test, the magnetometer achieved an instrumental accuracy of 0.2 nT (characterized under stable observatory conditions) and a noise floor of 0.09 nT, with Pearson correlations of 93.76–94.13% against reference scalar magnetometers. In the sea trial, the attitude-corrected, vector-synthesized total field agreed with two co-deployed Sentinel magnetometers at 230 m and 380 m depths, yielding Pearson correlations of 94.33% and 94.59%, respectively. All instruments coherently recorded diurnal variations with a peak-to-peak amplitude of approximately 50 nT. The inter-depth differences in mean total field—35,353 nT at 230 m, 35,337 nT at 380 m, and 35,285 nT at 580 m—are primarily attributable to uncalibrated instrument baselines, with secondary contributions from residual attitude correction errors. These results demonstrate that mooring platforms can support multi-depth vector geomagnetic observations over deployment timescales of weeks to months, providing a pathway toward spatially distributed deep-sea geomagnetic field monitoring.